Environmentally friendly methods for controlling pine pitch canker. (27th March 2019) - Martín‐García, J.; Zas, R.; Solla, A.; Woodward, S.; Hantula, J.; Vainio, E. J.; Mullett, M.; Morales‐Rodríguez, C.; Vannini, A.; Martínez‐Álvarez, P.; Pinto, G.; Alves, A.; et al.
Abstract : Fusarium circinatum is a highly virulent invasive pathogen that causes the disease commonly known as pine pitch canker (PPC). On mature trees, the most common symptoms of PPC include resin bleeding, resinous cankers, wilting of needles and dieback. In nurseries the main symptoms are yellowish needles, and wilting of foliage and shoots. PPC is considered one of the most important diseases of conifers globally and at least 60 species of Pinus along with Pseudotsuga menziesii are known to be susceptible. Quarantine regulations are crucial to minimize the risk of new introductions into disease‐free countries. However, if these measures fail, implementation of environmentally friendly control methods is currently encouraged in an integrated management approach that minimizes the use of chemicals in forests. This review therefore summarizes current knowledge of biological control using endophytic fungi, bacteria and viruses, and other environmentally friendly methods to control PPC, including thermotherapy, natural products with fungicidal effects, promoters of innate host resistance mechanisms and breeding for resistance. Key research gaps to be addressed for improvement of effective management of this disease are discussed.